Effects of Ta Content on Thermodynamic Properties and Transformation Temperatures of Shape Memory NiTi Alloy - Dagdelen, F.; Kok, M.; Qader, I. N. (Korean Inst Metals Materials, 2019)
In the present work, Ni32-x-Ti-Ta18+x (x = 0, 2, 3, 4, 5, 6, 7, 8) shape memory alloys, produced by arc-melting method. Then, differential scanning calorimetry (DSC), optical microscopy (OM), x-ray diffraction (XRD), and Vickers micro-hardness measurements were carried out to investigate thermodynamic parameters, microstructure, crystal structure, and mechanical properties of the alloys, respectively. The DSC results showed that, as the amount of Ta increased, the phase transformation temperatures of the specimens significantly changed. In addition, increasing of Ta composition raised the mass density and electron participation of NiTi alloy, and thus, the vibrational term of entropy overcomes the electron participation; consequently, the total entropy declined in the alloys. It is found that OM images possess a dendritic microstructure, where by increasing the amount of Ta, the dendrites length increase while random orientations decrease. Moreover, XRD patterns exhibited the existence of each austenite phase (B2), martensite phase (B19MODIFIER LETTER PRIME), and beta-Ta riched phase in all samples.
Keywords: Shape memory alloy; Phase transformation; NiTiTa alloy; Thermal stability; Microstructure